2021
DOI: 10.3389/fcimb.2021.716789
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Inhibiting Activity of Cefoperazone and Its Metallic Derivatives on Pseudomonas aeruginosa

Abstract: The last decade has witnessed a massive increase in the rate of mortalities caused by multidrug-resistant Pseudomonas aeruginosa. Therefore, developing new strategies to control virulence factors and pathogenicity has received much attention. One of these strategies is quorum sensing inhibition (QSI) which was developed to control Pseudomonas infection. This study aims to validate the effect of one of the most used β-lactam antibiotics; cefoperazone (CFP) and its metallic-derivatives on quorum sensing (QS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The LuxI enzyme produces the QS signal molecule (the N-3-oxo-hexanoyl-homoserine lactone), and LuxR is a transcription regulator that binds to the AHL signal and regulates bioluminescence via the luxCDABEG operon [ 9 ]. Following the discovery of the AHL-QS system, researchers discovered that AHL-QS is prevalent in a wide range of Proteobacteria and influences vital characteristics such as motility [ 10 ], pigment production [ 11 ], and biofilm formation [ 12 ]. Our molecular understanding of the QS system has been useful in studying plant–microbe, animal–microbe, and human–microbe interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The LuxI enzyme produces the QS signal molecule (the N-3-oxo-hexanoyl-homoserine lactone), and LuxR is a transcription regulator that binds to the AHL signal and regulates bioluminescence via the luxCDABEG operon [ 9 ]. Following the discovery of the AHL-QS system, researchers discovered that AHL-QS is prevalent in a wide range of Proteobacteria and influences vital characteristics such as motility [ 10 ], pigment production [ 11 ], and biofilm formation [ 12 ]. Our molecular understanding of the QS system has been useful in studying plant–microbe, animal–microbe, and human–microbe interactions.…”
Section: Introductionmentioning
confidence: 99%
“…11 Cefoperazone sodium is a long-acting cephalosporin with a strong antibacterial effect on a variety of Gram-negative aerobic and anaerobic bacteria, but it has poor resistance to β-lactamases produced by various bacteria, such as Enterococcus and Pseudomonas aeruginosa. 15 A study by Kuo et al 16 showed that sulbactam sodium can significantly enhance the antibacterial 17 also demonstrated that a stepwise increase in the ratio of sulbactam to partner β-lactam antibiotics led to a stepwise decrease in the minimum inhibitory concentrations (MICs) and a stepwise increase in the susceptibility rates. Ratio 1:3 of cefoperazone/ sulbactam resulted in 91% sensitivity rate of Acinetobacter Baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…Cefoperazone (CFP, Figure 15 b) is one of the most widely used β-lactam antibiotics. Some researchers tried to explore some other activities of CFP, and its metallic derivatives cefoperazone iron complex (CFPF) and cefoperazone cobalt complex (CFPC) were found to interact more strongly with LasI, LasR, and PqsR receptors than CFP, CFPF, and CFPC and to eliminated QS-associated virulence factors [ 115 ]. Hadizadeh et al found that oxicams (piroxicam and meloxicam, Figure 15 b) can serve as the best inhibitors of LasR from the studied nonsteroidal anti-inflammatory drug (NSAID) compounds and also have potential antagonist activity against PqsE in the pqs system [ 116 ].…”
Section: Inhibitors Acting On Multiple Qs Systemsmentioning
confidence: 99%